2021
DOI: 10.1021/acs.langmuir.1c01173
|View full text |Cite
|
Sign up to set email alerts
|

Are Contact Angle Measurements Useful for Oxide-Coated Liquid Metals?

Abstract: This work establishes that static contact angles for gallium-based liquid metals have no utility despite the continued and common use of such angles in the literature. In the presence of oxygen, these metals rapidly form a thin (∼1−3 nm) surface oxide "skin" that adheres to many surfaces and mechanically impedes its flow. This property is problematic for contact angle measurements, which presume the ability of liquids to flow freely to adopt shapes that minimize the interfacial energy. We show here that advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 77 publications
0
73
0
Order By: Relevance
“…To address these issues, we have previously presented the use of a liquid metal as a liquid with a barely measurable evaporation rate [22] and demonstrated robotically assisted contact angle measurements in a scanning electron microscope (SEM) [23]. To address the issue of oxide layer growth on the liquid metal droplets, which would prevent them from being useful for contact angle measurements [24], our experiments take place in the low-oxygen vacuum atmosphere of an SEM chamber.…”
Section: Introductionmentioning
confidence: 99%
“…To address these issues, we have previously presented the use of a liquid metal as a liquid with a barely measurable evaporation rate [22] and demonstrated robotically assisted contact angle measurements in a scanning electron microscope (SEM) [23]. To address the issue of oxide layer growth on the liquid metal droplets, which would prevent them from being useful for contact angle measurements [24], our experiments take place in the low-oxygen vacuum atmosphere of an SEM chamber.…”
Section: Introductionmentioning
confidence: 99%
“…NaOH (1M) was used as an electrolyte to create a basic pH environment that dissolves the surface oxide of the liquid metal, 37 which would otherwise interfere with the wetting dynamics and contact angle. 38 The dissolution of gallium oxide proceeds through the following reaction 39 Ga O 2NaOH 3H O 2Na Ga(OH) Resonant Frequency. The resonant frequency (ω) of a freely oscillating liquid droplet for the nth mode oscillation is given as 41−43 ω 2 = (σ LV n(n − 1)(n + 2)/ρ)q 3 , where σ LV is the interfacial tension of the liquid metal and surrounding electrolyte interface, n is the mode number, ρ is the density of EGaIn, and q is the characteristic length of the droplet.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Prior to electrode printing, the contact angles made by water and EGaIn on the composite (PGNC@6wt %) were compared to that of pure PDMS and no significant difference was observed (Figure 7a-d) which indicated negligible changes in surface wetting behaviors by the GNF fillers. Receding the EGaIn droplets left behind traces of oxide (Figure 7e-h) which signifies oxide-substrate adhesion possibly by van der Waals interaction [89]. Using the camera of the contact angle goniometer, tilting of a tiny droplet of pure EGaIn on composite was recorded (Video S1) and it was observed that the droplet adhered to the composite even when the tilt angle was 90 • , signifying resistive adhesive force of the droplet's oxide layer to the composite's surface against gravitational force [38].…”
Section: Oxidized Egain As Soft and Stretchable Electrodementioning
confidence: 96%